2018
DOI: 10.3389/fimmu.2018.02485
|View full text |Cite
|
Sign up to set email alerts
|

Improving Immunotherapy Through Glycodesign

Abstract: Immunotherapy is revolutionizing health care, with the majority of high impact “drugs” approved in the past decade falling into this category of therapy. Despite considerable success, glycosylation—a key design parameter that ensures safety, optimizes biological response, and influences the pharmacokinetic properties of an immunotherapeutic—has slowed the development of this class of drugs in the past and remains challenging at present. This article describes how optimizing glycosylation through a variety of g… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
44
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 51 publications
(45 citation statements)
references
References 393 publications
(427 reference statements)
0
44
0
Order By: Relevance
“…Chlamydomonas reinhardtii has been suggested as a potential biofactory for the production of protein‐based pharmaceuticals (Barrera and Mayfield, ; Mathieu‐Rivet et al , ; Rasala and Mayfield, ; Hempel and Maier, ). A substantial portion of the protein‐based pharmaceuticals, such as monoclonal antibodies and erythropoietin, are glycosylated proteins (Walsh, ; Mathieu‐Rivet et al , ), and it is well established that the N ‐glycosylation of the protein represents a critical quality attribute influencing the half‐life of the protein, its biological activity, as well as its safety and immunogenicity (Lingg et al , ; Buettner et al , ; Mimura et al , ). Indeed, glyco‐epitopes that are absent in mammalian cells could be immunogenic when proteins carrying such decorations are injected into humans (van Beers and Bardor, ).…”
Section: Discussionmentioning
confidence: 99%
“…Chlamydomonas reinhardtii has been suggested as a potential biofactory for the production of protein‐based pharmaceuticals (Barrera and Mayfield, ; Mathieu‐Rivet et al , ; Rasala and Mayfield, ; Hempel and Maier, ). A substantial portion of the protein‐based pharmaceuticals, such as monoclonal antibodies and erythropoietin, are glycosylated proteins (Walsh, ; Mathieu‐Rivet et al , ), and it is well established that the N ‐glycosylation of the protein represents a critical quality attribute influencing the half‐life of the protein, its biological activity, as well as its safety and immunogenicity (Lingg et al , ; Buettner et al , ; Mimura et al , ). Indeed, glyco‐epitopes that are absent in mammalian cells could be immunogenic when proteins carrying such decorations are injected into humans (van Beers and Bardor, ).…”
Section: Discussionmentioning
confidence: 99%
“…The potential of glycosylation engineering to enhance therapeutics has been investigated and utilized extensively in the field of protein biopharmaceuticals, for example in anticancer antibodies. 102,103 Cell-based therapies are emerging fast in the treatment of diverse diseases, including autoimmune diseases and cancer. In order to enhance the function of therapeutic cells, extensive studies are being performed seeking for improved survival, proliferation and differentiation of these cells.…”
Section: Glycan-engineering and Implications In Immune Therapymentioning
confidence: 99%
“…Protein glycosylation is proved to have a profound impact on the molecular interactions modulating the immune system, thus reacting upon a row of physicochemical and pharmacokinetic parameters of immunotherapeutic drugs for treating cancer and other pathologies. For example, sialylation on the termini of the N-glycan branches on the immunotherapeutics results in a higher negative charge of the glycoproteins and increases their half-life by masking the penultimate galactose moiety from the hepatocyte asialoglycoprotein receptor and thus preventing endocytosis to prolong circulatory lifetime [51]. Besides, it was shown that Fc hypersialylation of therapeutic antibodies might influence the IgG interaction with the neonatal Fc receptor extending the half-life of IgG by reducing their intracellular degradation [52].…”
Section: Glycans In Cancermentioning
confidence: 99%
“…The presence of α-Gal on the monoclonal antibodies was shown to be associated with the possibility of hypersensitivity reactions while treating with Cetuximab, an epidermal growth factor receptor inhibitor, used in metastatic colorectal cancer [57]. That is why monitoring of terminal galactose groups is one of the quality control parameters in the production of immunotherapeutics [51].…”
Section: Glycans In Cancermentioning
confidence: 99%